Goatkeepers' guide - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Innovations in goat keeping in humid West and Central Africa: a tool for extension agents by HA G Koper-Limbourg and D O Oyeyemi 1993 51pp